The relationship between conflict and employee performance at Universiti Sultan Zainal Abidin (UniSZA), Gong Badak Campus / Noor Amirah Fasihah Ramly - Ramly, Noor Amirah Fasihah (2014)
This research investigates the relationship between conflicts an employee performance, in Universiti Sultan Zainal Abidin (UniSZA), Campus Gong Badak. The literature provided discusses the three independent variables Such as relationship conflict, task conflict and organizational conflict and dependent variables is an employee performancc. Information was gathered, using questionnaire instruments. It is a main instrument in the research. The questionnaire comprises five (5) sections For this study, the appropriate questions will develop by the researcher. The first section is Section A includes the demographic information backgrounds, second is Section B that focused on relationship conflict, Section C is task conflict. For the Section D is organizational conflict and for the last section is Section E that involves the employee pertormance. This question will use 5 point Likert scale with the following vat which are 1=Very Low, 2-Low, 3- Moderate, 4-High, 5-Very High. Ail data obtained from each of the research instruments was then statistically analysed. Simple correlation analysis showed that there is a positively relationship between conflicts and employee performance. As this research takes place in Universiti Sultan Zainal Abidin (UniSZA), Campus Gong Badak, it contributes to the educational industry of findings relating to the concepts of research.